High anti-TNFα Concentrations Are Not Associated With More Adverse Events in Pediatric Inflammatory Bowel Disease. Issue 6 (December 2021) - Zvuloni, Maya; Matar, Manar; Levi, Rachel; Shouval, Dror S.; Shamir, Raanan; Assa, Amit
Abstract : ABSTRACT: Anti-tumor necrosis factor alpha (anti-TNFα) therapy is commonly used to treat refractory pediatric inflammatory bowel disease (IBD) and carry risks for adverse events. We aimed to assess the relationship between anti-TNFα trough concentrations and adverse events rate among pediatric patients with IBD. The medical records of pediatric patients with IBD who were treated with anti-TNFα agents from 2015 to 2020 and had sequential monitoring of trough concentration (TC) were reviewed retrospectively for the presence of adverse events. The study cohort included 135 eligible patients (59 [43.7%] girls, mean age at diagnosis 12.9 [±3] years, 111 [82.2%] Crohn disease) who had 1589 measurements of TCs (1037 [63%] infliximab). During a median follow-up period of 1.7 years (IQR 1.1–2.7), we recorded 156 adverse events in 50 patients (37%). Higher TCs were not associated with higher rate of anti-TNFα-related adverse events whereas these events (excluding increase in liver transaminases) were associated with younger age.